(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The aim of this research is to study the changes that were made to the role of the President of the Republic in Iran, after the 1979 Constitution was subjected to amendments in 1989. Moreover, the impact of these amendments on the president’s power in general. This is by reviewing the ruling institutions and the fundamental amendments that have made to the 1979 Constitution, and affected the powers of the President of the Republic. The descriptive and legal approaches were used to determine the most prominent amendments, and to what extent the president’s role was affected by the amendments that were introduced to the constitution.